THE USE OF WEBLOG TO IMPROVE STUDENTS’ ABILITY IN READING NARRATIVE TEXT: A Pre-Experimental Research - Syam , Ita Adryani; Abdul, Nurdevi Bte; Saiful (FKIP Unismuh Makassar, 2018)
This research aimed finding the improvement of the students’ ability in reading narrative text by using Weblog. The writer applied pre-experimental method and collected the data based on the test. The sample of the research was class X MIA 2 of SMA Muhammadiyah Limbung that consisted of 29 students. The sample was taken by using purposive sampling technique. The research findings showed that the students had poor score in pre-test. After treatment, their reading ability in narrative text increase significantly. The result of the research were the mean score of reading narrative text in term of identify. Orientation obtained by the students through pre-test was 66 and posttest was 80 (21.2%), with the t-test value was greater than t-table (11.4 > 2.04). Complication obtained by the students through pre-test was 66 and posttest was 79 (19.7%) with the t-test value was greater than t-table (9.9>2.04). Resolution obtained by the students through pre-test was 70 and posttest was 79 (12.9%) with the t-test value was greater than t-table (3.8 > 2.04). The result of calculating t-test. Students in reading narrative text was greater than t-table (25.1>2.04). It was concluded that the use of Weblog improved students’ ability in reading narrative text.